The curse of bad geography: Stagnant water, diseases, and children's human capital - Steve Berggreen; Linn Mattisson (Lund University, School of Economics and Management, Department of Economics, 2023)
Waterborne diseases lead to over 6 billion diarrheal episodes per year, with most of the burden on children in low-income countries. We employ hydrological engineering principles to construct a novel measure of stagnant water, crucial to the spread of these diseases. Using a difference-in-differences approach, we estimate the causal effect of stagnant water on the health and cognitive skills of Tanzanian children. A 10 percentage point increase in stagnant water increases local diarrhea incidence rates among children by 30%. Our results also show an immediate reduction in the cognitive abilities of affected children, measured by standardised test scores. The effects on health and cognition are exacerbated by high temperatures and population density, but are completely mitigated by access to safe water and sanitation. We find that two degrees Celsius of global warming could triple the burden of waterborne diseases, and that disease awareness in high-risk locations remains low, which could motivate targeted information campaigns. Our results show how stagnant water exposure in areas with inadequate water and sanitation may result in millions of children failing to reach their cognitive potential.
Keywords: I14; I15; O15; Q53; Q54; 330; Waterborne Diseases; Stagnant Water; Child Health; Tanzania; Climate Change